2015
DOI: 10.1099/vir.0.000147
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human papillomavirus type 16 particles with heparan sulfate and syndecan-1 molecules in the keratinocyte extracellular matrix plays an active role in infection

Abstract: Oncogenic human papillomaviruses (HPVs) attach predominantly to extracellular matrix (ECM) components during infection of cultured keratinocytes and in the rodent vaginal challenge model in vivo. However, the mechanism of virion transfer from the ECM to receptors that mediate entry into host cells has not been determined. In this work we strove to assess the role of heparan sulfate (HS) chains in HPV16 binding to the ECM and determine how HPV16 release from the ECM is regulated. We also assessed the extent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 62 publications
2
62
0
Order By: Relevance
“…Inhibiting HPA activity dramatically reduces the release of the HPV16 virus from the extracellular matrix, as well as cellular uptake and infection. Conversely, exogenous HPA can activate this process [21]. HPV E6 and E7 proteins, two main carcinogenic proteins, can cause cellular transformation via their actions on multiple signal transduction pathways [22].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting HPA activity dramatically reduces the release of the HPV16 virus from the extracellular matrix, as well as cellular uptake and infection. Conversely, exogenous HPA can activate this process [21]. HPV E6 and E7 proteins, two main carcinogenic proteins, can cause cellular transformation via their actions on multiple signal transduction pathways [22].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, because the PsVs were lost from the BM under furin inhibition, data suggested that the conformational change that exposed the furin cleavage site on the capsid also resulted in a decreased binding affinity of the viral capsid for the HSPG [35]. An in vitro study found that furin cleavage was not required for PsVs to be transferred from the ECM to the cell surface [40]. It was concluded that HS-processing enzymes (heparanase and MMPs) are responsible for the release of ECM-bound virus since ECM binding of the virus is mediated via HS chains of shed syndecan-1 ectodomains [40].…”
Section: Binding and Cell Surface Receptors Of Hpv16mentioning
confidence: 99%
“…An in vitro study found that furin cleavage was not required for PsVs to be transferred from the ECM to the cell surface [40]. It was concluded that HS-processing enzymes (heparanase and MMPs) are responsible for the release of ECM-bound virus since ECM binding of the virus is mediated via HS chains of shed syndecan-1 ectodomains [40]. Another in vitro study showed that PsVs with a mutated furin/PC cleavage site can bind to cells and be internalized [33].…”
Section: Binding and Cell Surface Receptors Of Hpv16mentioning
confidence: 99%
“…While integrin α6 mediates virus binding directly, other integrins could be involved indirectly by recruiting other well-established primary receptors such as heparan sulfate proteoglycans (HSPGs) [15][16][17][18] . Alternatively, integrins could mediate outside-in activation of signalling pathways 19 , which could link external virus binding to intracellular processes like endocytosis 20 .…”
Section: Anatomy Of a Viral Entry Platform Differentially Functionalimentioning
confidence: 99%